Зміст та особливості компетенції Державного бюро розслідувань України в сфері діяльності правоохоронних органів в умовах воєнного стану - Лісойван, Я. М.; Lisoivan , Ya. M. (Актуальні питання у сучасній науці. - 2023. - № 12(18). - С. 576-587, 2023)
У статті досліджено поняття та особливості компетенції Державного бюро розслідувань України в сфері діяльності українських правоохоронних органів. Наведенні позиції вітчизняних вчених щодо визначення поняття «компетенція», його зміст та співвідношення з поняттям «повноваження». Запропоновано авторське визначення поняття «компетенція Державного бюро розслідувань України», під якою слід розуміти сукупність його владних повноважень, закріплених у нормативно-правових актах відповідно до покладених на нього завдань і функцій, які визначають можливості Державного бюро розслідувань України приймати обов’язкові до виконання рішення, організовувати та контролювати їх належне виконання у правоохоронній сфері. Наголошено, що основною особливістю компетенції ДБР України на відміну від інших правоохоронних органів є те, що працівники ДБР наділенні повноваженнями щодо викриття і розслідування злочинів, учинених вищими посадовими особами (службовими особами) органів державної влади, суддями та працівниками правоохоронних органів, військовослужбовцями.

The article examines the concepts and features of the competence of the State Bureau of Investigation of Ukraine in the sphere of activity of Ukrainian law enforcement agencies. Citations of the position of domestic scientists regarding the definition of the concept of "competence", its content and relationship with the concept of "authority". It was noted that the competence of the law enforcement body should be considered through its internal structure, because it is not homogeneous. Competence consists of a number of interrelated elements, which should include: 1) normatively established goals; 2) subjects of knowledge as legally defined spheres and objects of interaction; 3) functions and powers as a legally guaranteed measure of decision-making and execution of actions; 4) responsibility for non-performance. The author's definition of the concept of "competence of the State Bureau of Investigation of Ukraine" is proposed, which should be understood as the totality of its powers enshrined in normative legal acts in accordance with the tasks and functions assigned to it, which determine the possibilities of the State Bureau of Investigation of Ukraine to make binding decisions, organize and monitor their proper implementation in the law enforcement sphere. Based on the content of the powers defined in the Law of Ukraine "On the State Bureau of Investigation", they can be conventionally divided into three main groups: 1) powers that characterize the State Bureau of Investigation of Ukraine as a pre-trial investigation body (powers that outline the rights and duties of employees SBI in the process of prevention, detection, termination, disclosure and investigation of crimes); 2) separate powers related to the participation of the SBI of Ukraine in state policy in the field of combating crime and international cooperation in law enforcement matters; 3) powers related to work with the personnel of the law enforcement agency, its information and analytical, personnel and material and technical support. It was emphasized that the main feature of the competence of the SBI of Ukraine, unlike other law enforcement agencies, is that SBI employees are empowered to expose and investigate crimes committed by high-ranking officials (officials) of state authorities, judges and employees of law enforcement agencies, and military personnel.

Проанализированы научные подходы украинских ученых к определению понятия «компетенция» и особенностей компетенции Государственного бюро расследований Украины в сфере деятельности правоохранительных органов Украины в условиях правового режима военного положения. Отмечено, что основной особенностью компетенции ГБР Украины , в отличие от других правоохранительных органов является то, что работники ГБР наделены полномочиями по разоблачению и расследованию преступлений, совершенных высшими должностными лицами органов государственной власти, судьями и работниками правоохранительных органов, военнослужащими.
Content and features of the competence of the State Bureau of Investigations of Ukraine in the field of the activities of law enforcement bodies under the conditions of the state of martial
Keywords: Державне бюро розслідувань України; State Bureau investigations of Ukraine; Государственное бюро расследований Украины; правоохоронні органи; law enforcement agencies; правоохранительные органы; компетенція; competence; компетенция; повноваження; powers; полномочия; адміністративно-правове регулювання; administrative and legal regulation; административно-правовое регулирование